Study Of Photocopier Film Distribution Flow - Adinda Ayu; Arinta Agustina; Trisna Pradita Putra (TUMATA: Journal of Arts and Cultural Management, 2023)
The process of distributing films can be understood as a way for a film to be introduced to the market and made accessible to its intended audience or viewers. Since the inception of the storyline concept by the production parties, the distribution plan has been readily available in the film industry. This implies that the distribution strategy has been a focus for the Producers and Directors even prior to engaging in the three essential stages of film production, namely pre-production, production, and post-production. Film, being a result of imaginative and artistic representation, cannot be dissociated from the cultural and societal environment which both creates and consumes it. Distribution strategies in the film industry need to be aligned with the ability to preserve the filmmaker's vision and aspirations, ensuring the movie is showcased in suitable screening venues and resonates with the intended audience. This Thesis contains research on the distribution channel of the film Photocopier, which was distributed to meet the audience or audiences that have been projected or designed from the start, and are intended to be marketed to. In the context of the film Photocopier, distribution has been carried out and aligned with the vision of the Director and Producer. Photocopier is the first feature film by Wregas Bhanuteja and as its distribution debut, Photocopier went according to expectations where this film managed to attain achievements, gain appreciation, and grow in reputation, as well as achieving financial success.